Synthesis, photophysicochemical properties and TD-DFT calculations of tetrakis(2-benzoyl-4-chlorophenoxy) phthalo-cyanines - Yilmaz, Yusuf; Mack, John; Sener, M. Kasim; Sonmez, Mehmet; Nyokong, Tebello (WORLD SCIENTIFIC PUBL CO PTE LTD, 2014)
The synthesis of metal free, magnesium and zinc tetrakis(2-benzoyl-4-chlorophenoxy) phthalocyanine derivatives (2-4) is described along with their characterization by elemental analysis, IR, UV-visible absorption, and 1H NMR spectroscopy and mass spectrometry. Trends observed in the fluorescence, triplet state, singlet oxygen and photodegradation quantum yields and the triplet state lifetimes are also analyzed. The compounds exhibit high solubility in a wide range of organic solvents and no evidence of aggregation was observed over a wide concentration range. The Zn(II) complex (4) was found to have a very high singlet oxygen quantum yield (Phi(Delta) = 0.78) in dimethylsulfoxide (DMSO) and a reasonably large triplet state quantum yield (Phi(T) = 0.82). The photophysical and photochemical properties clearly demonstrate that these compounds could prove useful in singlet oxygen applications such as photodynamic therapy (PDT). DFT and TD-DFT calculations were used to assess the impact of the positional isomerism of the 2-benzoyl-4-chlorophenoxy substituents on the electronic structures and optical spectroscopy.
Keywords: phthalocyanine; singlet oxygen quantum yields; TD-DFT calculations; OXYGEN QUANTUM YIELDS; PHOTOCHEMICAL PROPERTIES; SINGLET OXYGEN; METAL-COMPLEXES; PHTHALOCYANINES; FLUORESCENCE; SUBSTITUENTS; DERIVATIVES; BEHAVIOR; ZINC(II); Chemistry